Revert daie : lived experiences of Indian preachers in Malaysia - Aemy Elyani Mat Zain,; Jaffary Awang,; Haslina Ibrahim,; Ahmad Faizuddin Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Preachers are people who deliver Islamic message or speech to the communities around them. This is because the agenda of preaching has been inherent in a Muslim and preaching is also one of the duties of the previous prophets. In Malaysia, the participation of non-Malay preachers such as Indian and Chinese preachers in delivering preaching is constantly growing from time to time. Furthermore, the involvement of Indian Muslims in the arena of preaching still receives less attention in academic studies, although it is undeniable that they also play a role in developing da'wah in Malaysia. It can be seen, most academic studies focus more on aspects of converts such as the welfare of converts, the management of converts to the Indian community and others. Therefore, the objective of this study is to explore the true story of four Indian preachers in the context of their experiences before embracing Islam and their involvement in preaching. The methodology of this study is qualitative and involves the collection of data in the field. The results of the study found that their strength as Indian Muslim preachers was influenced by three elements, (i) their life and experience before embracing Islam, (ii) their exposure in the diversity of knowledge and, (iii) the external support that makes them have their own approach and principles in delivering da'wah.